A G protein γ subunit-like domain shared between RGS11 and other RGS proteins specifies binding to G(β5) subunits - Snow, Bryan E. (The National Academy of Sciences, 1998)
Regulators of G protein signaling (RGS) proteins act as GTPase-activating proteins (GAPs) toward the α subunits of heterotrimeric, signal-transducing G proteins. RGS11 contains a G protein γ subunit-like (GGL) domain between its Dishevelled/Egl-10/Pleckstrin and RGS domains. GGL domains are also found in RGS6, RGS7, RGS9, and the Caenorhabditis elegans protein EGL-10. Coexpression of RGS11 with different G(β) subunits reveals specific interaction between RGS11 and G(β5). The expression of mRNA for RGS11 and G(β5) in human tissues overlaps. The G(β5)/RGS11 heterodimer acts as a GAP on G(αo), apparently selectively. RGS proteins that contain GGL domains appear to act as GAPs for G(α) proteins and form complexes with specific G(β) subunits, adding to the combinatorial complexity of G protein-mediated signaling pathways.